Mutual fund investors perception in India-a study - Udhayasankar, R.; Maran, K. (International Journal of Engineering and Technology, 2017)
Mutual fund is four decades old in India.  It was started by UTI during the year 1964 with few schemes for small investors. During this short span of time it has made tremendous growth in Indian small investors. But now a day’s its volume of investors and sources of investment also growing tremendous level. Moreover mutual fund scheme have added new dimension to overcome financial risk of small investors and also in fund raising capacity of corporate sectors. Mutual fund investors can diversify even more by purchasing different kind of stocks which will helps to spreading out investors’ money across different types of derivative instruments and hence it reduces the risk tremendously up to certain extent and it is automatically diversify in a predetermined category of investments. This serves bridge work between small investors and corporate sectors likewise considering those points in this paper is an attempt to know the investors’ perceptions towards selected mutual funds. This paper makes an attempt to identify various factors affecting perception of investors regarding investment in mutual funds. The findings will helpful to identify the investors’ interest base and factors clearly and it reveals that the investors consider mutual funds as flexible investment option and it creates interest of investment among small investors.